A hyperbranched conjugated Schiff base polymer network: a potential negative electrode for flexible thin film batteries. Issue 14 (19th January 2016) - Sun, Yubao; Sun, Yahui; Pan, Qiyun; Li, Gai; Han, Bo; Zeng, Danli; Zhang, Yunfeng; Cheng, Hansong
Abstract : A hyperbranched conjugated Schiff base polymer network was synthesized by condensation between 4, 4′, 4′′-nitrilotribenzaldehyde and p -phenylenediamine. Abstract : A hyperbranched conjugated Schiff base polymer network was synthesized by condensation between 4, 4′, 4′′-nitrilotribenzaldehyde and p -phenylenediamine. The material exhibits excellent rate capability and long cycle life for lithium storage. Coupled with lower electrode potential (0.7 V vs. Li + /Li), it may be well suited for fully flexible thin film polymeric batteries as the negative electrode.